Archaeal viruses at the cell envelope: entry and egress - Quemin, Emmanuelle R. J.; Quax, Tessa E. F. (Frontiers in Microbiology, 2015)
The cell envelope represents the main defense of host that viruses encounter on their way from one cell to another. The cytoplasmic membrane in general is a physical barrier that needs to be crossed both upon viral entry and exit. Therefore, viruses from the three domains of life employ a wide range of strategies for perforation of the cell membrane, each adapted to the cell surface environment of their host. Here, we review recent insights on entry and egress mechanisms of viruses infecting archaea. Due to the unique nature of the archaeal cell envelope, these particular viruses exhibit novel and unexpected mechanisms to traverse the cellular membrane.